The Influence of User Interface Component on University Website Towards Student Enrollment - Alexander, Onki; Ishak, Zurida; ., . (International Journal of Engineering and Technology, 2018)
Website interface can be a very effective communication medium between the university and the users such as potential students, current students and other authorities. The purpose of this study is to investigate interface components that represent important information in university website, which led to the enrollment of students. This study is motivated by the user frustration or thwarted by the frequent usability problems of university website and problem in representing important information into required by potential students. The interface component and the important information on university website are identified through a comprehensive literature review. There are several factors that influence the student's decision process such as tuition fees, scholarship, ratings / reputation, vicinity to home and the majors offered. The interface components that are used in this research are metaphor, navigation, mental model, interactions and appearance. This study will produce the interface design guideline based on the most frequent used of interface component. Analysis of 5 universities has been conducted to identify how the important information, which leads to studentâ€™s enrollments is presented on the interface.Â